2023
DOI: 10.3389/fimmu.2023.1212163
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise as a friend not a foe in acute kidney diseases through immune system modulation

Ana Carolina Costanti-Nascimento,
Leonilia Brelaz-Abreu,
Elayne Bragança-Jardim
et al.

Abstract: Regular and moderate exercise is being used for therapeutic purposes in treating several diseases, including cancer, cardiovascular diseases, arthritis, and even chronic kidney diseases (CKDs). Conversely, extenuating physical exercise has long been pointed out as one of the sources of acute kidney injury (AKI) due to its severe impact on the body’s physiology. AKI development is associated with increased tubular necrosis, which initiates a cascade of inflammatory responses. The latter involves cytokine produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…The authors identified several risk factors involved in the development of AKI where the precondition of patients can determine AKI severity. Interestingly, Costanti-Nascimento et al 75 proposed the prescription of moderate and regular aerobic exercise for patients who are at risk of developing AKI and for those diagnosed with AKI. In this present study, we observed that preconditioning by MIAE attenuated the development of gentamicin-induced AKI and reduced kidney injury biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified several risk factors involved in the development of AKI where the precondition of patients can determine AKI severity. Interestingly, Costanti-Nascimento et al 75 proposed the prescription of moderate and regular aerobic exercise for patients who are at risk of developing AKI and for those diagnosed with AKI. In this present study, we observed that preconditioning by MIAE attenuated the development of gentamicin-induced AKI and reduced kidney injury biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in IL-6 levels after exercise is only a temporary response, and the result of long-term exercise intervention is a decrease in plasma IL-6 levels [24]. Costanti-Nascimento et al [25] showed that moderate exercise can regulate the immune system to develop in an anti-inflammatory direction in diabetic kidney injury, and exercise can reduce the expression of inflammatory factors and TGF-β and alleviate oxidative stress to in order alleviate diabetic kidney injury. Therefore, exercise may reduce inflammatory and fibrotic factors, as well as alleviate oxidative stress in the kidneys to play a protective role.…”
Section: Protective Role Of Exercise Against Dn In Human Studiesmentioning
confidence: 99%